Collecting from the margins : material culture in a Latin American context - Andrade, María Mercedes, 1971- (Bucknell University Press : Copublished by the Rowman & Littlefied Publishing Group, 2016)
Collecting from the Margins: Material Culture in a Latin American is the first anthology to provide a sustained discussion of the modern practice of collecting from a specifically Latin American perspective. Spanning the period after the independence wars until the 1980s, this collection of ten essays addresses the continuities and discontinuities of Latin American collecting practices, both private and public, in a wide variety of literary texts and historical texts.